ANALISIS PENGGUNAAN TEKNOLOGI PESAWAT TANPA AWAK DALAM MENDUKUNG OPERASI PENGAMANAN DI WILAYAH PERBATASAN DARAT RI-RDTL - Sutaji Sutaji; Rudi Lazuardi; Agustinus Bandur (Jurnal Teknologi, 2022)
Indonesia is an archipelagic state that has land and sea boundaries with other countries. One of the land border areas of the Republic of Indonesia (RI) is the Democratic Republic of Timor Leste (RDTL). In order to protect the RI-RDTL land border area, the Indonesian Armed Forces (TNI) has deployed the RI-RDTL Border Security Task Force. The border security system implemented by the RI-RDTL Border Security Task Force has not been able to fully monitor the border area as a whole, so violations often occur in the RI-RDTL land border area that are not monitored. In order for the RI-RDTL Border Security Task Force to be more effective in carrying out its duties in protecting the RI-RDTL land border area, it needs to be equipped with Unmanned Aerial Vehicle (UAV) technology. The purpose of this study was to analyze the effectiveness of the use of UAV technology in supporting security operations in the RI-RDTL land border area with the measured effectiveness indicators covering aspects of Reliability, Adaptability, Sustainability, Interoperability, Risk, Cost, Time and Human. This research uses Mixed Methods with Concurrent Embedded methods. Qualitative data were processed using NVivo 12 Plus software and analyzed using descriptive analytical methods. While quantitative data is processed using SPSS 26 software and Measures of Effectiveness (MoE). The results of this research conclude that UAV technology is effectively used to support security operations in the RI-RDTL land border area with a final effectiveness value of 0.829 for all UAV effectiveness indicators that have been determined.